Concept of Jihad in The Qur’an (A Moderate and Contextual Approach in The Contemporary Era) - Dirno, Dirno (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study discusses the interpretation of verses on jihad in the Qur'an, emphasising the importance of a moderate and contextual approach in facing contemporary challenges. To date, the concept of jihad has often been misunderstood and reduced to only the aspect of war (qital), leading to misinterpretations that result in violence, extremism, and even terrorism. In fact, the Qur'an uses the term jihad in various contexts that indicate a broad meaning, including spiritual, intellectual, socio-economic, and physical jihad. This research method uses a qualitative approach with descriptive analysis related to modern interpretations based on primary sources (the Qur'an) and secondary sources (classical and contemporary interpretations). This study shows that classical interpretations emphasise jihad as defensive warfare due to the historical context of Muslims at that time, while contemporary interpretations emphasise maqashid al-syari'ah, so that jihad is interpreted as a comprehensive struggle to uphold the values of humanity, justice, and peace. The results of the study show that jihad is a multidimensional concept that cannot be narrowed down to violence. Jihad is a spiritual energy that drives Muslims to build civilisation, uphold tawhid, and fight against various forms of falsehood and injustice. A moderate understanding of jihad has important implications, not only for Muslims in maintaining their internal unity, but also for the global community in creating harmony, tolerance, and peace.